2019
DOI: 10.1039/c8tc05904g
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Based tin sulfide Sr3MnSn2S8 with a wide band gap and strong nonlinear optical response

Abstract: The new nonlinear optical material Sr3MnSn2S8 is a noncentrosymmetric structure with a large band gap of 3.02 eV. In addition, Sr3MnSn2S8 possesses a good second harmonic generation (SHG) response, approximately equivalent to that of AgGaS2, and a high laser damage threshold (LDT) about 3 times that of AgGaS2 (AGS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Sr 3 MnSn 2 S 8 has a three-dimensional structure, and the basic unit of Sr 3 MnSn 2 S 8 is composed of [MnS 4 ] and [SnS 4 ] tetrahedra passing through the common corner. In the case of [SnS 4 ] tetrahedra, one Sn atom is connected to four S atoms . In comparison, Rb 10 Zn 4 Sn 4 S 17 has the same zero-dimensional structure as K 10 Zn 4 Sn 4 S 17 , and it belongs to the cubic structure of asymmetric space group P 43 m .…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Sr 3 MnSn 2 S 8 has a three-dimensional structure, and the basic unit of Sr 3 MnSn 2 S 8 is composed of [MnS 4 ] and [SnS 4 ] tetrahedra passing through the common corner. In the case of [SnS 4 ] tetrahedra, one Sn atom is connected to four S atoms . In comparison, Rb 10 Zn 4 Sn 4 S 17 has the same zero-dimensional structure as K 10 Zn 4 Sn 4 S 17 , and it belongs to the cubic structure of asymmetric space group P 43 m .…”
Section: Structurementioning
confidence: 99%
“…Additionally, Sr 3 MnSn 2 S 8 shows an almost identical second harmonic generation (SHG) coefficient to that of the benchmark AgGaS 2 , and its LDT is about 3 times that of AgGaS 2 . 26 Moreover, it was found that the band gaps of the compounds into which manganese is introduced are smaller than those into which zinc is introduced. 27−31 The band gap of ZnS 32 has been reported to be larger than that of MnS; 33 similarly, the band gap of Li 2 ZnSnS 4 21 is more prominent than that of Li 2 MnSnS 4 .…”
mentioning
confidence: 99%
“…The α-Pb 2 GeS 4 structure type is an extremely robust crystal structure and is capable of several substitutions. Many compounds adopting this crystal structure have been characterized, and some have had their NLO properties reported as well. The substitution variant Na 0.5 Pb 1.75 GeS 4 was found to exhibit a large second harmonic generation (SHG) signal . Sr 0.25 Pb 1.75 GeSe 4 was first predicted by Kanatzidis et al to exist after reporting that the monovalent cations Na + and Ag + could be substituted into Pb 2 GeSe 4 due to partially occupied Pb sites in the structure .…”
Section: Introductionmentioning
confidence: 99%
“…The new ternary and quaternary chalcogenides are gradually approved as promising materials for its NLO properties and the transparent region which can be modulated with the composition. AgGaGeS 4 crystal is just one of the solid solution crystal AgGaS 2 – n GeS 2 ( n = 1) and becomes a popular research subject. , It has a high nonlinear optical coefficient ( d 31 = 15 pm/V), a wide transmission range (0.5–11.5 μm), and a low residual absorption coefficient (0.05 cm –1 at 1.064 μm), which make it a promising material for frequency-shifting 1.064 μm Nd:YAG laser into the range of 4–11 μm. However, the other AgGaS 2 – n GeS 2 ( n = 2, 3, 4, and 5) crystals, i.e., AgGaGe 2 S 6 , AgGaGe 3 S 8 , AgGaGe 4 S 10 and AgGaGe 5 S 12 , which are rarely reported, also have the comparable NLO properties. The nonlinear optical coefficients of AgGaGe 3 S 8 and AgGaGe 4 S 10 crystal are d 31 = 13.65 and 13.8 pm/V, respectively, which are very close to that of AgGaGeS 4 .…”
Section: Introductionmentioning
confidence: 99%